Conformational changes in dough with pumpkin protein concentrate for wheat flour bakery products - Shevchenko, Anastasiia; Litvynchuk (Vorontsova), Svitlana (My University, 2023)
The range of food products, in particular bakery products, is represented mostly by traditional types with a rather low nutritional and biological value. The solution to this problem can be the inclusion in the formulation of such products of sources of complete proteins, such as pumpkin protein concentrate, which, in combination with the lipid component, will be useful for people with diseases of the gastrointestinal tract, such as irritable bowel syndrome. The reflection spectra of wheat flour and pumpkin protein concentrate showed slight differences. The spectrum of wheat flour had a higher reflection intensity. Samples of dough after fermentation had a lower reflectance along the entire length of the spectrum than raw materials and dough after kneading. The infrared spectra of the bread samples were compared to the corresponding dough samples after fermentation. A characteristic extremum characterizing the amino acid composition was observed at a wavelength of 2294 nm. Taking into account the mentioned transformations and the ability of pumpkin protein concentrate to significantly increase the biological value of bread, its use in the production technology of wheat bakery products is promising and relevant in order to give bread healthy properties.
Keywords: dough; infrared spectroscopy; bread; pumpkin protein concentrate; кафедра технології хлібопекарських і кондитерських виробів; кафедра фізики та професійної безпеки